Antioxidant and toxicological properties of essential oils and aqueous extracts of three aromatic herbs of Alentejo - Piçarra, A. (2015)
Plants are constituted for diverse bioactive compounds that are found to be important, like antioxidants compounds that are often found in secondary metabolite in plants and are useful in prevention of some diseases (neurodegenerative and others) and oxidative stress [1] In present work we develop a set of studies for evaluation of antioxidant and toxicological properties of essential oils (EOs) and aqueous extracts of some aromatic plants from Alentejo, namely Calamintha nepeta (L.) Savi subsp nepeta (calamint), Rosmarinus officinalis L. (rosemary) and Foeniculum vulgare L. (fennel). EOs were extracted from aerial parts of these plants by hydrodistillation and aquoes extracts were obtained by lyophilization of the corresponding hydrolates [2]. Antioxidant activities were determined by three methods: DPPH radical, -carotene/linoleic acid and reducing power assay. Toxicity of EOs and hydrolates was carried out by the brine shrimp mortality test (LC50) and evaluation of acute toxicity (DL50) in mice. Additionally, the serum levels of some enzymes as biomarkers of liver and kidney function (AST, ALT, ALP, -GT, creatinine and bilirubin) were performed.